Academic abilities and glycaemic control in children and young people with Type 1 diabetes mellitus - Semenkovich, K.; Patel, P. P.; Pollock, A. B.; Beach, K. A.; Nelson, S.; Masterson, J. J.; Hershey, T.; Arbeláez, A. M. (Diabetic medicine, 2016)
Aims To determine if children and young people aged < 23 years with Type 1 diabetes differ in academic ability from age‐matched control subjects without Type 1 diabetes and whether academic scores are related to glycaemic control. Methods Using a cross‐sectional study design, we administered cognitive and academic tests (Woodcock‐Johnson III Spatial Relations, General Information, Letter‐Word Recognition, Calculation and Spelling tests) to young people with Type 1 diabetes (n=61) and control subjects (n=26) aged 9–22 years. The groups did not differ in age or gender. Participants with Type 1 diabetes had a disease duration of 5–17.7 years. History of glycaemic control (HbA1c, diabetic ketoacidosis and severe hypoglycaemic episodes) was obtained via medical records and interviews. Results The participants with Type 1 diabetes had a lower mean estimated verbal intelligence (IQ) level compared with those in the control group (P=0.04). Greater exposure to hyperglycaemia over time was associated with lower spelling abilities within the group with Type 1 diabetes (P=0.048), even after controlling for age, gender, socio‐economic status, blood glucose level at time of testing and verbal IQ (P=0.01). History of severe hypoglycaemia or ketoacidosis was not associated with differences in academic abilities. Conclusions In children and young people, Type 1 diabetes was associated with a lower verbal IQ. Moreover, increased exposure to hyperglycaemia was associated with lower spelling performance. These results imply that hyperglycaemia can affect cognitive function and/or learning processes that may affect academic achievement. What's new? Children and young people aged < 23 years with Type 1 diabetes performed less well on verbal intelligence tests than healthy control subjects. Subjects with greater exposure to hyperglycaemia had a lower spelling performance than those with less degree of hyperglycaemia exposure. Effects on spelling performance were not explained by age, gender, IQ, socio‐economic status or blood glucose values at time of testing.